Biochemical Properties of a Bushmaster Snake Venom Serine Proteinase (LV-Ka), and Its Kinin Releasing Activity Evaluated in Rat Mesenteric Arterial Rings - Maria L.D. Weinberg; Liza F. Felicori; Cynthia A. Bello; Henrique P.B. Magalhães; Alvair P. Almeida; Arinos Magalhães; Eladio F. Sanchez (Elsevier, 2004)
A serine proteinase with kallikrein-like activity (LV-Ka) has been purified to homogeneity from bushmaster snake (Lachesis muta muta) venom. Physicochemical studies indicated that LV-Ka is a single chain glycoprotein with a molecular mass (Mr) of 33 kDa under reducing conditions which was reduced to 28 kDa after treatment with N-Glycosidase F (PNGase F). LV-Ka can be bounded and neutralized by serum α2-macroglobulin (α2-M), a prevalent mammalian protease inhibitor that is capable of forming a macromolecular complex with LV-Ka (Mr >180 kDa). Cleavage of α2-M by the enzyme resulted in the formation of 90-kDa fragments. The proteolytic activity of LV-Ka against dimethylcasein could be inhibited by α2-M, and the binding ratio of the inhibitor:enzyme complex was found to be 1:1. The Michaelis constant, Km, and catalytic rate constant, kcat, of LV-Ka on four selective chromogenic substrates were obtained from Lineweaver-Burk plots. LV-Ka exhibits substrate specificities not only for the glandular kallikrein H-D-Val-Leu-Arg-pNA (S-2266) but also for the plasmin substrates S-2251 and Tos-Gly-Pro-Lys-pNA. Bovine kininogen incubated with LV-Ka generated a polypeptide that dose dependently contracted mesenteric arterial rings from spontaneously hypertensive rats (SHR) in a similar way as bradykinin (BK) does. As it happens with BK, LV-Ka generated polypeptide was inhibited by HOE-140, a bradykinin B2-receptor antagonist and by indomethacin, a cyclo-oxygenase inhibitor. These results strongly suggest that the polypeptide generated by LV-Ka by cleavage of bovine kininogen is bradykinin. In addition, our studies may help to understand the mechanism of action involved in hypotension produced by envenomation of bushmaster snake. Keywords:: serine proteinase, bradykinin, snake venom, Lachesis, mesenteric arterial ring